Burnout and job performance: A case study of psychology faculty at a university in Quito (National Administration Journal, 2025)
The primary objective of this study was to evaluate the job performance of faculty members at a university located in Quito, Ecuador, and to identify the potential presence of emotional exhaustion related to their academic duties. Additionally, the study aimed to explore a possible relationship between burnout syndrome and teaching performance.A quantitative approach with a correlational research design was employed. The study population consisted of 92 faculty members. Data were collected from primary sources through the application of the Maslach Burnout Inventory (MBI)[1] and from secondary sources, using the results of faculty performance evaluations provided by the university.Findings indicate that only 18% of the participants exhibited signs of burnout. Overall, most faculty members demonstrated satisfactory job performance. Moreover, no statistically significant evidence was found to support a direct relationship between burnout syndrome and professional teaching performance.Based on these findings, a series of recommendations are proposed at the individual, interpersonal, and organizational levels, aimed at preventing and mitigating the effects of burnout within the academic environment studied.[1] Christina Maslach et al., Maslach Burnout Inventory Manual: General Survey, Human Services Survey, Educators Survey, and Scoring Guides (Palo Alto, CA: Mind Garden, 1986), http://www.mindgarden.com.
Keywords: Burnout syndrome; teaching performance; emotional exhaustion; job performance